Natural Is Not Always Better: The Varied Effects of a Natural Environment and Exercise on Affect and Cognition - Trammell, Janet P.; Aguilar, Shaya C. (Frontiers in Psychology, 2021)
The Attention Restoration Theory has been widely cited to account for beneficial effects of natural environments on affect and attention. However, the effects of environment and exercise are not consistent. In a within-subjects design, participants completed affective and cognitive measures that varied in attentional demands (memory, working memory, and executive function) both before and after exercise in a natural and indoor environment. Contrary to the hypotheses, a natural environment resulted in lower positive affect and no difference in negative affect compared to an indoor environment. A natural environment resulted in the most improvement for cognitive tasks that required moderate attentional demand: Trail Making Test A and Digit Span Forwards. As predicted, exercise resulted in improved affect and improved executive function (Trail Making Test B). There were no interactions between environment and exercise. These results suggest that Attention Restoration Theory cannot fully explain the influence of environment on affect and cognition.